2016
DOI: 10.18632/oncotarget.8355
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing quantified methylation level of BRCA1 promoter as prognostic factor for survival in breast cancer patient

Abstract: BRCA1 promoter methylation is an essential epigenetic transcriptional silencing mechanism, related to breast cancer (BC) occurrence and progression. We quantified the methylation level of BRCA1 promoter and evaluated its significance as prognostic and predictive factor. BRCA1 promoter methylation level was quantified by pyrosequencing in surgical cancerous and adjacent normal specimens from 154 BC patients. A follow up of 98 months was conducted to assess the correlation between BRCA1-methylation level vs. ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Previous experimental studies have suggested that mechanisms other than mutations (e.g. epigenetic modifications) may alter BRCA1 expression and/or subcellular distribution in breast cancer [ 16 ]. This study has investigated BRCA1 protein expression and subcellular localization, and their relation to clinicopathological characteristics in a population-based study of an ethnically diverse sample of breast cancer patients using two different staining methods, IHC versus dual IF, and automated digital microscopy analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies have suggested that mechanisms other than mutations (e.g. epigenetic modifications) may alter BRCA1 expression and/or subcellular distribution in breast cancer [ 16 ]. This study has investigated BRCA1 protein expression and subcellular localization, and their relation to clinicopathological characteristics in a population-based study of an ethnically diverse sample of breast cancer patients using two different staining methods, IHC versus dual IF, and automated digital microscopy analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However the majority of studies included in the meta-analysis used methylation-specific PCR or other methods that do not distinguish individual CpG sites, limiting mechanistic interpretation. Even a recent study of BRCA1 promoter methylation using pyrosequencing analysed the results by averaging the methylation levels across all sites, thus not utilizing the CpG site-specific results generated by pyrosequencing [ 42 ]. The considerable heterogeneity between studies highlights the difficulties in drawing meaningful conclusions when different CpG sites have been studied, methylation detection methods used, populations studied and tissues examined [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of BRCA1 nuclear expression correlates with high tumor grade and ER-negative tumors [17]. Absent or reduced BRCA1 expression in tumors without BRCA1 pathogenic variants appears to be linked to hypermethylation of the BRCA1 promoter region [18], a condition reported in 9.1-37% of sporadic BCs and associated with infiltrating ductal carcinoma type, high tumor grade (grade II-III), ER negativity, basal marker expression, younger age at diagnosis, and poor prognosis [18][19][20][21][22][23][24][25][26][27][28][29]. Thus, BRCA1 promoter hypermethylation could be a marker of BRCA1 deficiency in the absence of BRCA1 mutation, as these two events appear to be almost mutually exclusive [23,[30][31][32][33][34], outside of the recently described association between a dominantly inherited 5' UTR variant, classified as likely pathogenic, and BRCA1 promoter hypermethylation [35].…”
Section: Introductionmentioning
confidence: 99%